2015
DOI: 10.17507/jltr.0606.14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dynamic Assessment on the Listening Skills of Lower-intermediate EFL Learners in Chinese Technical College: A Pilot Study

Abstract: Abstract-The dynamic assessment, based on Vygotsky's sociocultural theory and the concept of zone of proximal development, has been considered capable of unifying assessment and instruction in the development of the assessee. This study aims to explore whether dynamic assessment can promote the integration of listening comprehension assessment and instruction while at the same time enhance students' study in listening. Five second-year English majors from a technical college in an underdeveloped area of a coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Hashemi Shahraki et al ( 2015 ) carried out a study to estimate test-takers’ listening conversational implicatures of pragmatic knowledge and conveyed that the mediational support improved their pragmatic grasp of conversational implicatures. For Wang ( 2015 ), DA of listening enhances the amalgamation of assessment and instruction.…”
Section: Defining Listeningmentioning
confidence: 99%
“…Hashemi Shahraki et al ( 2015 ) carried out a study to estimate test-takers’ listening conversational implicatures of pragmatic knowledge and conveyed that the mediational support improved their pragmatic grasp of conversational implicatures. For Wang ( 2015 ), DA of listening enhances the amalgamation of assessment and instruction.…”
Section: Defining Listeningmentioning
confidence: 99%
“…Further, it was concluded that correct application of DA approaches helps the researcher make use of reflections and lesson plan reform to develop learners' knowledge. In a parallel result, after applying dynamic approaches on five second-year English majors from a technical college, Wang (2015) reported that interventionist DA is able to realize lower intermediate EFL learners' listening comprehension potentials and develop problem solving behaviors among these learners. It was also concluded that integrating assessment and listening instruction can implement DA requirements to promote mental and future development.…”
Section: Related Studiesmentioning
confidence: 98%
“…of DA has led to strategic recommendations in curriculum development. Wang [14] analysed the contributions of DA on Chinese EFL learners. The researcher selected five participants for the experiment.…”
Section: Studymentioning
confidence: 99%